Perancangan Ruang Fisioterapi dan Rehabilitasi Stroke dengan Konsep Arsitektur Rustic - Andi Sahputra Depari; Zaneta Immanuela Kang; Fairuz Insyirah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
An architectural approach is a method that can accommodate various societal issues. Such an approach takes into consideration these problems to resolve them architecturally. In the modern era, there are various approaches that can be implemented according to the issues at hand, including those for improving healthcare facilities, especially in densely populated areas. The healthcare facilities catering to stroke rehabilitation, particularly in Balikpapan city, are still insufficient considering the city's population, which reaches hundreds of thousands of people. In this study, the researcher examines the application of rustic architecture approach to address the needs of healthcare facilities in the study area. The research not only focuses on the rehabilitation spaces but also on the physiotherapist's residence. Literature review, data collection, analysis, and design processes have been conducted to produce design options for the rustic architectural approach for physiotherapy residential and rehabilitation workspace specifically for stroke healthcare facilities. The findings of this research serve as foundational study to aid stakeholders in formulating designs for healthcare facilities, particularly for stroke rehabilitation